Alhuqûl ad dalâliyah bayna al musthalahât al mutarâdifah wa atsaruhâ fî fahmi alqur’ân - Moh. Ismail (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
One of the superiority of the Al-Qur'an is the accuracy of the meaning of words. And to understand the true meaning of the structure of the Qur'an can be done by detecting the phenomenon of language, including the phenomenon of equations and the relationship between the meaning of words. The equation of meaning in the Al-Qur’an is a broad subject, so it takes great effort in analyzing the meaning of synonyms, the most important being the analysis of the original meaning to the analysis of the structure context, and the semantic relationship between the two. The semantic relationship is the basis of communication and understanding among members of human society and in understanding the meaning of the words of the Al-Qur'an, this is the essence of linguistics and what is the purpose of the study of sound, morphology and grammar. This research takes words that have synonyms as an example of research, namely الدين ,الملة , العلم and المعرفة. The researcher's view that the words